An Iconic Odd Couple: The Hagiographic Rehabilitation of Epiphanius and John Chrysostom - Kim, Young Richard (Church history, 2018)
When saints utter prophetic words, they must in some way come true, at least in the hagiographic tradition. But what if one holy person curses another (and vice versa)? Such was the case between Epiphanius and John Chrysostom during the so-called Origenist Controversy, which ensued at the end of the fourth century and into the fifth. Epiphanius, working at the behest of Theophilus of Alexandria, was suspicious of John's orthodoxy and accused him of harboring Origenist fugitives. Epiphanius played the provocateur, traveling to Constantinople and conspiring to discredit John and cast doubts on his leadership, while John did his best to accommodate his elderly colleague from Cyprus. Their differences, however, were irreconcilable. In the end, each bishop wished a dubious fate for the other, both of which came true: Epiphanius died on his journey home, and John was deposed twice and died in exile. Yet both are revered as preeminent fathers of the church, and so in order to reach a point in which they could be counted together as saints, a process of hagiographical rehabilitation and selective forgetfulness began soon after their respective deaths.